2021
DOI: 10.1186/s13741-021-00206-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative physiotherapy on signs and symptoms of pulmonary collapse and infection after major abdominal surgery: secondary analysis of the LIPPSMAck-POP multicentre randomised controlled trial

Abstract: Background Preoperative education and breathing exercise training by a physiotherapist minimises pulmonary complications after abdominal surgery. Effects on specific clinical outcomes such as antibiotic prescriptions, chest imaging, sputum cultures, oxygen requirements, and diagnostic coding are unknown. Methods This post hoc analysis of prospectively collected data within a double-blinded, multicentre, randomised controlled trial involving 432 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Moreover, these improvements in physical functional and nutritional status continued up to 4 weeks postoperatively, which created favorable conditions for comprehensive postoperative treatment. Te results of our trial showed that the rate of pulmonary infections in patients in the prehabilitation group was signifcantly lower than that in the control group, indicating that the prehabilitation interventions can reduce the occurrence of perioperative pulmonary infections, which is also consistent with existing literature [37]. In contrast, there was no signifcant diference in the incidence of abdominal complications between the two groups, indicating that the improvement of physical function and the improvement of nutritional level had no signifcant efect on the prevention of abdominal complications.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, these improvements in physical functional and nutritional status continued up to 4 weeks postoperatively, which created favorable conditions for comprehensive postoperative treatment. Te results of our trial showed that the rate of pulmonary infections in patients in the prehabilitation group was signifcantly lower than that in the control group, indicating that the prehabilitation interventions can reduce the occurrence of perioperative pulmonary infections, which is also consistent with existing literature [37]. In contrast, there was no signifcant diference in the incidence of abdominal complications between the two groups, indicating that the improvement of physical function and the improvement of nutritional level had no signifcant efect on the prevention of abdominal complications.…”
Section: Discussionsupporting
confidence: 91%
“…There is less evidence about the value of prehabilitation, which is, however, suggested as appropriate, or even necessary, both for the prevention of postoperative complications and the best outcome of surgery [68,69], as well as for the favorable cost-effectiveness it offers [70]. Based on the existing literature on both the benefits of aerobic exercise on cardiorespiratory health and functionality in patients with hip fractures [17,64], the positive regulation it brings about in biochemical markers such as hypercoagulability [22,23] and albumin [71,72], we hypothesize that a pre-and postoperative exercise program can provide a comprehensive, multidimensional and multisystemic benefit to patients after a hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…These complications occur due to atelectasis or severe pneumonia that may lead to respiratory failure or death. 6,7 The PPC complication makes prolonged treatment of the patients from the recovery room and the post-surgical room to fully recover. PPC is a common term for pulmonary complications after a surgical operation.…”
Section: Discussionmentioning
confidence: 99%
“…These complications occur due to atelectasis or severe pneumonia that may lead to respiratory failure or death. 6,7 PPC is a common term for pulmonary complications after a surgical operation. The reported incidence of this complication ranged from 1 to 40%, depending on the definitions of PPC and the types of surgery.…”
Section: Introductionmentioning
confidence: 99%